1973
DOI: 10.1139/p73-163
|View full text |Cite
|
Sign up to set email alerts
|

Transport Properties of the Ferromagnetic Metals. I. Cobalt

Abstract: The thermal conductivity, electrical resistivity, and thermoelectric power of well-characterized, polycrystalline specimens of pure Co have been determined in the temperature range of 90 to 1250 K. Additionally, the measurements of the electrical resistivity have been extended to 1750 K, and the coefficient of thermal expansion measured between 300 and 770 K. The new results are compared with those previously published, and, for the low temperature h.c.p. phase, compared with predictions based on published ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 0 publications
6
20
0
Order By: Relevance
“…By contrast, the present Co/Cu multilayers have an fcc structure and the lateral grain size is also definitely larger than in the previously studied electrodeposited Co since this is a prerequisite for the observation of a significant GMR. On the other hand,  0 (300 K) = 6 cm was reported for well-annealed, defect-free bulk hcp-Co by Laubitz et al 55 These latter authors have also reported data 55 from which we can see that around the temperature of the hcp-fcc transition of bulk Co (at about 700 K) the resistivity of the fcc phase is by about 8 % smaller than that of the hcp phase. By assuming an identical temperature dependence of  for both phases, we can assess  0 (300 K) = 5.5 cm for bulk fcc-Co. On the other hand, we can estimate an incremental resistivity of about 0.5 cm for the magnetic layer due to the small amount of Cu in it (this value is obtained under the plausible assumption that the resistivity increase due to alloyed Cu is the same for the Ni-Cu and the Co-Cu systems in their fcc phases and taking the incremental resistivity of Cu reported for fcc-Ni 49 ).…”
Section: A Zero-field Electrical Resistivitysupporting
confidence: 63%
“…By contrast, the present Co/Cu multilayers have an fcc structure and the lateral grain size is also definitely larger than in the previously studied electrodeposited Co since this is a prerequisite for the observation of a significant GMR. On the other hand,  0 (300 K) = 6 cm was reported for well-annealed, defect-free bulk hcp-Co by Laubitz et al 55 These latter authors have also reported data 55 from which we can see that around the temperature of the hcp-fcc transition of bulk Co (at about 700 K) the resistivity of the fcc phase is by about 8 % smaller than that of the hcp phase. By assuming an identical temperature dependence of  for both phases, we can assess  0 (300 K) = 5.5 cm for bulk fcc-Co. On the other hand, we can estimate an incremental resistivity of about 0.5 cm for the magnetic layer due to the small amount of Cu in it (this value is obtained under the plausible assumption that the resistivity increase due to alloyed Cu is the same for the Ni-Cu and the Co-Cu systems in their fcc phases and taking the incremental resistivity of Cu reported for fcc-Ni 49 ).…”
Section: A Zero-field Electrical Resistivitysupporting
confidence: 63%
“…3 with bulk literature thermopower values for Co 14 and Cu 15 . The Co film grown at a base pressure of 6 x 10 −10 torr has a lower resistivity and larger thermopower than the second Co film grown at a base pressure of 1 x 10 −10 .…”
Section: Resultsmentioning
confidence: 68%
“…As explained above, the thermopower for Co/Cu and Ni/Cu multilayers is estimated from the literature values for bulk in reference to Pt 16,21,[76][77][78] . Since the composition has a stronger influence than the layer thicknesses, the Co-Ni to Cu ratio is set to 5:1.…”
Section: B Magnetothermopowermentioning
confidence: 99%